Thomas Mann papers - Mann, Thomas, 1875-1955.; Mann, Thomas, 1875-1955.
Letters (1909-1928) from Mann to Julius Bab, holograph draft of Das Gesetz (1944), and drafts of speeches delivered at the Library of Congress (1942-1947).
Novelist and essayist. Consultant in German literature, Library of Congress.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection related to the Library of Congress Archives.
Keywords: Bab, Julius, -- 1880-1955 -- Correspondence; Literature; Essayists; Novelists